Socio‐Ecological Impacts of the Investment of Urban Nature in Heat Mitigation for Two Megacities - Jing Wang; Weiqi Zhou; Timon McPhearson; Elizabeth M. Cook; Pablo Herreros‐Cantis; Jing Liu (Earth's Future, 2025)
Abstract Cities are increasingly adapting green interventions meant to enhance climate resilience, given their capacity to provide numerous ecosystem services (ES). Yet, little is known about ecological and social impacts of such interventions in the context of socio‐ecological framework and environmental justice. Here, we used a quantitative and spatial analytical approach to assess the changes of urban greenspace (UG) and examine the equity of changes in ES supply and demand across demographic and socioeconomic groups in Beijing and NYC between 2010 and 2017. Results showed that previously existing green space and its expansion were unevenly distributed across districts. High‐income districts in NYC had high green cover and experienced the highest increase of UG, in contrast to high green cover in areas with low population density and the greatest increase of UG in high‐income areas for Beijing, respectively. The inequitable distribution of UG resulted in a high level of mismatch in supply demand of ES, revealing a pattern of distributional ecological injustice within city. We also found more ecological supply was provided in the areas having less vulnerability, indicating that social vulnerability remained in a lower greenspace exposure after greening implementation in both cities. Our study contributes to a better understanding on how the dynamics of urban greenspace impact urban climate injustices, and provides new insights for critical urban adaptation interventions or practice on shaping ecological injustice.